Mercu Suar Nelayan di Desa Maja Lampung Selatan - Panuju, Achmad Yahya Teguh; Harun, Suryadiwansa; Ibrahim, Gusri Akhyar; Tarkono (Nemui Nyimah, 2024)
This community service project aimed to provide a simple lighthouse solution in Maja Village, Kalianda, South Lampung. The primary issue faced by local fishermen was the lack of navigation guidance during nighttime sailing due to blocked light from residential houses by the coastal seawall. The proposed solution involved the construction of two solar-powered lighthouses, designed to provide sufficient brightness and withstand coastal environmental conditions. This activity was carried out through collaboration between students, village officials, and the community, following a method that included problem identification, product design formulation, lamp pole construction, and installation. The results demonstrated that both lighthouses functioned optimally in assisting fishermen’s navigation, improving safety, and supporting night fishing activities. Additionally, the use of solar energy introduced the community to the concept of sustainable renewable energy.